False positivity of gamma-glutamyl transpeptidase measurement in urine - Crivellenti, Leandro Zuccolotto [UNESP]; Mesa, Javier Sousa [UNESP]; Wilkes Burton Meirelles, Adriana Erica [UNESP]; Crivellenti, Sofia Borin [UNESP]; Mireya, Edna Gomes [UNESP]; Canola, Julio Carlos [UNESP]; Hatayde, Mario Roberto [UNESP]; Santana, Aureo Evangelista [UNESP]; Dantas, Marcio; Barros Silva, Gyl Eanes (Informa Healthcare, 2014)
Although enzymuria tends to be associated to renal injury, there are no studies that have evaluated the presence of the enzyme gamma-glutamyl transpeptidase (GGT) spectrophotometry in the urine using a non-nephrotoxic agent (Nerium oleander) in order to evaluate the possibility of false positive results. The urinary GGT/urinary creatinine concentration ratio (uGGT/uCr) of 10 healthy dogs was calculated and posteriorly confronted with data from clinical evaluation, hematological and serum biochemical profiles, creatinine clearance (CrC), urinalysis, urine protein/creatinine ratio (UPC), electrocardiogram, systemic blood pressure (SBP) and light and electron microscopy. The results for kidney histology, SBP, UPC and CrC were not significantly different in any of the time-points analyzed. However, uGGT/uCr was significantly higher when measured 4 hours and 24 hours after administration of N. oleander. The measurement of the urinary GGT enzyme, as performed in many studies, yielded false positive results in dogs poisoned by a non-nephrotoxic agent.
Keywords: Enzymuria; GGT/urinary creatinine; Kidney; nephrotoxicity